2020
DOI: 10.21082/jti.v44n1.2020.31-36
|View full text |Cite
|
Sign up to set email alerts
|

Microclimate Condition in the Natural Ventilated Greenhouse

Abstract: A Greenhouse has a different microclimate compared to the outside field. Climate parameters such as solar radiation and air temperature are important parameters that affect plant growth and productivity. This research aims to understand the relation of climate factors in the inside and outside Greenhouse, the effect of microclimate on evapotranspiration and to predict the amount og evapotranspiration inside the Greenhouse. Microclimate analysis was held in two stages, the firststage was from February 5 to Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…A. Hoyo et al (Hoyo et al 2019) suggested a control approach based on the feedback linearisation technique and quantitative feedback theory to regulate the interior diurnal temperature in a greenhouse in the south of Spain. Vita Ayu Kusuma Dewi et al (Dewi et al 2020) study the relationship between climatic conditions within and outside the greenhouse, the influence of microclimate on evapotranspiration, and the ability to forecast evapotranspiration inside the greenhouse. The evapotranspiration value follows the climate condition due to the varied environment within and outside the greenhouse.…”
Section: Temperature Control In Greenhousementioning
confidence: 99%
“…A. Hoyo et al (Hoyo et al 2019) suggested a control approach based on the feedback linearisation technique and quantitative feedback theory to regulate the interior diurnal temperature in a greenhouse in the south of Spain. Vita Ayu Kusuma Dewi et al (Dewi et al 2020) study the relationship between climatic conditions within and outside the greenhouse, the influence of microclimate on evapotranspiration, and the ability to forecast evapotranspiration inside the greenhouse. The evapotranspiration value follows the climate condition due to the varied environment within and outside the greenhouse.…”
Section: Temperature Control In Greenhousementioning
confidence: 99%
“…Parameter yang paling mempengaruhi pertumbuhan dan produktivitas tanaman adalah radiasi matahari dan suhu udara (Dewi, Setiawan, Waspodo, & Liyantono, 2020). Radiasi matahari di dalam rumah tanaman di saat siang hari jauh lebih rendah dibandingkan di luar rumah tanaman.…”
Section: Parameter Cuaca Dan Kelembaban Tanahunclassified
“…Studies on the heterogeneous microclimate in typical greenhouses in Central China [15], the development of microclimate models for predicting temperatures in naturally ventilated greenhouses [16], and the formulation and validation of mathematical models of greenhouse microclimates [17] are crucial for our approach. The exploration of greenhouse environment modeling and simulation for microclimate control by [18,19], as well as the works on microclimate conditions in naturally ventilated greenhouses [20], and the optimization of greenhouse microclimate parameters [21] considering the impact of CO 2 and light, make significant contributions.…”
Section: Introductionmentioning
confidence: 99%